2004
DOI: 10.1111/j.1931-2393.2004.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Infrequency of Sexually Transmitted Disease Screening Among Sexually Experienced U.S. Female Adolescents

Abstract: CONTEXT: Since 1993, the Centers for Disease Control and Prevention and professional medical organizations have recommended that all sexually experienced female adolescents receive annual screening for Chlamydia trachomatis. Whether adolescents receive this care is largely unknown. METHODS:Reports of receipt of testing or treatment for a sexually transmitted disease (STD) in the past year, as well as sites of care, were obtained from 3,987 sexually experienced females in grades 7-12 who participated in Wave 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 22 publications
(9 reference statements)
1
23
0
Order By: Relevance
“…In contrast, adolescent females who had a mother with less than a high school degree were more likely to have received services than those adolescents who had a mother with a college degree or more. This finding is in accordance with previous studies in which vulnerable populations were more likely to receive reproductive healthcare services (Fiscus et al, 2004;Porter & Ku, 2000;Schuster et al, 1996). Although the lack of social disparities in contraceptive services revealed in this study is encouraging, several factors may play a role in the receipt of reproductive services among vulnerable populations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, adolescent females who had a mother with less than a high school degree were more likely to have received services than those adolescents who had a mother with a college degree or more. This finding is in accordance with previous studies in which vulnerable populations were more likely to receive reproductive healthcare services (Fiscus et al, 2004;Porter & Ku, 2000;Schuster et al, 1996). Although the lack of social disparities in contraceptive services revealed in this study is encouraging, several factors may play a role in the receipt of reproductive services among vulnerable populations.…”
Section: Discussionsupporting
confidence: 93%
“…Although few studies have examined social disparities in adolescents' reproductive healthcare (Elster, Jarosik, VanGeest, & Fleming, 2003), evidence suggests that minority (Fiscus, Ford, & Miller, 2004;Porter & Ku, 2000;Schuster, Bell, Petersen, & Kanouse, 1996) and publicly insured adolescents (Fiscus et al, 2004;Porter & Ku, 2000) may be more likely to receive counseling on safer sexual practices (Porter & Ku, 2000;Schuster et al, 1996) and sexually transmitted infection testing (Fiscus et al, 2004;Porter & Ku, 2000) than White and privately insured adolescents. Reasons for the greater receipt of services in these studies may be that providers target certain populations due to concerns over increased risk (Fiscus et al, 2004;Porter & Ku, 2000).…”
mentioning
confidence: 99%
“…In fact, each year after 2008 (beginning of study period) conferred a 26% increase in contraceptive provision compared with preceding year. The higher occurrence of contraceptive provision in our older patients (16-25 years) may have been driven by a bias held by some pediatric providers regarding a perceived low incidence of sexual intercourse [10][11][12] and, by inference, lower teratogenic risk in younger girls (ie, 14-15 years). However, this assumption is inconsistent with established literature.…”
Section: Discussionmentioning
confidence: 99%
“…27 Other studies reported even lower chlamydia screening coverage than the national estimate of 60%. 28,29 A study among young female enrollees (aged 16 -26 years) in commercial and Medicaid health plans documented low and minimal increase in screening coverage of chlamydia. 28 The screening coverage for commercial health plans increased from 20% in 1999 to 26% in 2001, and for Medicaid plans, from 28% in 1999 to 38% in 2001.…”
Section: Discussionmentioning
confidence: 99%